2021
DOI: 10.3855/jidc.14025
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Incubation Period and Serial Interval for SARS-CoV-2 in Jiangxi, China, and an Updated Meta-Analysis

Abstract: Introduction: This paper aims to estimate the incubation period and serial intervals for SARS-CoV-2 based on confirmed cases in Jiangxi Province of China and meta-analysis method. Methodology: Distributions of incubation period and serial interval of Jiangxi epidemic data were fitted by “fitdistrplus” package of R software, and the meta-analysis was conducted by “meta” package of R software. Results: Based on the epidemic data of Jiangxi, we found the median days of incubation period and serial int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…One study used case data from multiple countries around the world, 81 6 studies were conducted in South Korea, 37 , 46 , 51 , 52 , 59 , 124 4 in France, 25 , 29 , 35 , 113 3 in Japan, 80 , 105 2 in Singapore, 87 , 111 2 in India, 16 , 78 , 83 , 103 2 in Vietnam, 21 , 58 and 2 in Australia. 45 , 99 One hundred nineteen studies (83.8%) included patients infected with the wild-type strain, 5 (3.5%) with the multiple strains, 17 , 26 , 35 , 80 , 112 and 11 (7.7%) with an unknown strain 84 , 93 , 99 , 106 , 116 , 126 , 135 , 142 , 148 , 150 , 157 (eTable 4 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…One study used case data from multiple countries around the world, 81 6 studies were conducted in South Korea, 37 , 46 , 51 , 52 , 59 , 124 4 in France, 25 , 29 , 35 , 113 3 in Japan, 80 , 105 2 in Singapore, 87 , 111 2 in India, 16 , 78 , 83 , 103 2 in Vietnam, 21 , 58 and 2 in Australia. 45 , 99 One hundred nineteen studies (83.8%) included patients infected with the wild-type strain, 5 (3.5%) with the multiple strains, 17 , 26 , 35 , 80 , 112 and 11 (7.7%) with an unknown strain 84 , 93 , 99 , 106 , 116 , 126 , 135 , 142 , 148 , 150 , 157 (eTable 4 in the Supplement ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is reasonable to assume that the intervention would not exert its effects immediately at the cut-off; hence, we opted for a lagged impact model with slope change only [17]. Bearing in mind the average incubation period of the virus [19][20][21], we tested each model with a cut-off established at six days from the intervention date.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated an incubation period of 3.4 days, based on case interview data from established, exclusive pairs with well‐defined, short exposure periods in a low‐prevalence population. Results from 14 meta‐analyses suggest an incubation period of five to six days 9-22 . Most published incubation period estimates, the basis of the meta‐analyses, are derived from studies of one of two exposure types – exposure to Wuhan 23-28 or to a confirmed COVID‐19 case 29-38 .…”
Section: Discussionmentioning
confidence: 99%